„Dirty, „Arty“ and „Red“ – Croatian Socialist Heritage out of Time and out of Memory - Potkonjak, Sanja; Pletenac, Tomislav (2011)
This paper aims at studying a Croatian continental town of Sisak and its identity-in-change regarding the political shifts after the 1990s. The town itself was a major industrial centre during socialism, prosperous and fast growing socialist locale. The paper here tries to observe the ways in which socialist political imagery, was materialized in architecture, public art and political rituals and was inscribed and embedded into the city. In particular, it focuses on the political trajectory of the last twenty years and the negotiations of socialist and post-socialist ideology, memory and collective identity regarding socialist art heritage. We would argue that by using the example of the ways in which socialist monuments were treated in the last twenty years in the town of Sisak we could as well claim that the period after 1990s shows strong processes of re-symbolization, the processes of modification of collective remembrance through public discourse and rituals. Symbolic capital of socialist monuments was questioned though the linguistic practices of neglect, aggression and hate, as well as by individual actions. The paper tries to set questions of how changes in political imaginary re-shape the collective imaginary of self and others, what makes particular stories become viable histories of the locale in contrast to the histories to be forgotten, and how is it that a city can offer a paradigm of changes, therefore revealing that a place becomes meaningful only upon the process of cumulative consensus upon its past and present.
Projekt MZOS
ENG